Kinetics of Innate Immune Response to Yersinia pestis after Intradermal Infection in a Mouse Model - Bosio, Christopher F. (American Society for Microbiology, 2012)
A hallmark of Yersinia pestis infection is a delayed inflammatory response early in infection. In this study, we use an intradermal model of infection to study early innate immune cell recruitment. Mice were injected intradermally in the ear with wild-type (WT) or attenuated Y. pestis lacking the pYV virulence plasmid (pYV(−)). The inflammatory responses in ear and draining lymph node samples were evaluated by flow cytometry and immunohistochemistry. As measured by flow cytometry, total neutrophil and macrophage recruitment to the ear in WT-infected mice did not differ from phosphate-buffered saline (PBS) controls or mice infected with pYV(−), except for a transient increase in macrophages at 6 h compared to the PBS control. Limited inflammation was apparent even in animals with high bacterial loads (10(5) to 10(6) CFU). In addition, activation of inflammatory cells was significantly reduced in WT-infected mice as measured by CD11b and major histocompatibility complex class II (MHC-II) expression. When mice infected with WT were injected 12 h later at the same intradermal site with purified LPS, Y. pestis did not prevent recruitment of neutrophils. However, significant reduction in neutrophil activation remained compared to that of PBS and pYV(−) controls. Immunohistochemistry revealed qualitative differences in neutrophil recruitment to the skin and draining lymph node, with WT-infected mice producing a diffuse inflammatory response. In contrast, focal sites of neutrophil recruitment were sustained through 48 h postinfection in pYV(−)-infected mice. Thus, an important feature of Y. pestis infection is reduced activation and organization of inflammatory cells that is at least partially dependent on the pYV virulence plasmid.